A Tale of β-Lactamases and Multidrug Resistance in Pseudomonas aeruginosa Isolated from Inpatients in a University Hospital - Yadav, Santosh K; Sharma, Sangita; Mishra, Shyam K; Sherchand, Jeevan B (Journal of Institute of Medicine Nepal, 2021)
Introduction In this era of modern medicine, antimicrobial resistance can be regarded as a major health calamity. The emergence of multidrug-resistant (MDR) Pseudomonas aeruginosa strains poses therapeutic challenges and lead to treatment failure in hospitalized patients. This study was conducted to determine various types of β-lactamases among MDR P. aeruginosa isolates recovered from hospitalized patients. Methods This study was conducted at Tribhuvan University Teaching Hospital, Maharajgunj, Nepal. The clinical samples collected from inpatients were processed for detection of P. aeruginosa isolates and antibiotic susceptibility profile was determined. The MDR strains were identified and ceftazidime-resistant isolates were subjected for detection of extended-spectrum-β-lactamase (ESBL), metallo-β-lactamase (MBL), and Klebsiella pneumoniae carbapenemase (KPC). Results A total of 161 P. aeruginosa isolates were recovered during the study period encompassing 73.3% (n=118) MDR isolates. The MDR isolates included 50.0% (n=59) from lower respiratory tract infections; and 39.8% (n=47) were from the intensive care unit patients. The MDR isolates showed a high resistance profile towards piperacillin, cephalosporins, and fluoroquinolones (>85%). Resistance to carbapenems and aminoglycosides were up to 80% and 60% respectively. Extended spectrum-β-lactamase, MBL, and KPC mediated resistance were seen in 34.7%, 43.6%, and 14.4% MDR isolates, respectively. Conclusion Multidrug resistance as well as resistance mediated by β-lactamases production were high among P. aeruginosa isolates. Therefore, early detection of antimicrobial resistance and rational use of antibiotics play a critical role to fight against this MDR pathogen.